Effect of Traditional Chinese Medicine Baduanjin exercise combined with remote ischemic conditioning on mild cognitive impairment after stroke (中医传统功法八段锦联合远隔缺血适应治疗脑卒中后轻度认知障碍的效果研究) - XUE CHAO (薛超); LI Juan (李娟); FANG Qian (方茜); CHEN Lihua (陈丽华); HAO Mingqing (郝明青); CHEN Zuoxiu (陈作秀) (中西医结合护理)
Objective To investigate the intervention effect of Traditional Chinese Medicine(TCM) Baduanjin exercise combined with remote ischemic conditioning therapy for patients with mild cognitive impairment in stroke. Methods Seventy patients with mild cognitive impairment after stroke were recruited as study subjects and randomly divided into control group(n=35) and intervention group(n=35). Patients in the control group received conventional treatment and care, and those in the intervention group received TCM Baduanjin exercise combined with remote ischemic conditioning therapy on the basis of conventional care. The cognitive function, daily living ability and quality of life of the two groups were compared before and after 12 weeks of intervention. Results After 12-week intervention, the scores of Montreal Cognitive Assessment (MoCA), Modified Barthel Index (MBI) and Stroke-specific Quality of Life Scale (SS-QOL) were significantly better than those before the intervention in both groups (P＜0. 01), and scores of the intervention group were significantly higher than those of control group (P＜0. 01). Conclusion TCM Baduanjin exercise combined with remote ischemic conditioning therapy is safe and effective for patients with mild cognitive impairment after stroke, and can improve overall cognitive function, daily living ability and quality of life. (目的 探讨脑卒中后轻度认知障碍患者应用中医传统功法八段锦联合远隔缺血适应治疗的干预效果。方法 选取2021年6月—2022年6月医院收治的70例脑卒中后轻度认知障碍患者为研究对象, 根据随机数字表分为对照组(n=35)和干预组(n=35)。对照组给予常规治疗和护理, 干预组在对照组基础上施以中医传统功法八段锦联合远隔缺血适应治疗。比较两组干预前、干预12周后的认知功能、日常生活能力和生活质量。结果 干预12周后, 两组蒙特利尔认知量表(MoCA)评分、改良巴氏指数(MBI)评分和脑卒中专用生活质量量表(SS-QOL)评分均较干预前上升(P＜0. 01), 且干预组评分高于对照组, 差异有统计学意义(P＜0. 01)。结论 中医传统功法联合远隔缺血适应治疗对脑卒中后轻度认知障碍患者安全有效, 能够改善整体认知功能, 提高日常生活能力及生活质量。)